STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP PERDA NO 12 TAHUN 2008 DALAM MEMBINA PENGAMEN ANAK DI KECAMATAN TAMPAN - Wasil Rahman; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by concerns about the exploitation of children and the many reasons for their poor family's economic background, causing them to take to the streets to find additional income for their family by singing. The formulation of the problem in this study is how to study public perceptions of regional regulation no 12 of 2008 in fostering child buskers in handsome sub-districts. The purpose of the study was to find out how the study of public perception of Perda No. 12 of 2008 in fostering child buskers in the district of handsome. The benefits of research results for students are to provide an overview of the study of public perception of Regional Regulation No. 12 of 2008 in fostering child buskers in the handsome sub-district and to be a reference for how to behave in a national institution according to a study of public perception of Regional Regulation No. 12 of 2008 in fostering buskers. boy in handsome district. This research was conducted in Tampan District in December 2020 – Mai 2021. This study used a quantitative descriptive method. The population in this study amounted to 194, 331 people. The sample in this study was taken using the Acidental sampling technique with a large number of 100 people from the whole community. So the results obtained in the above recapitulation are in the range of 18.6% + 29.4% = 48%. Thus, it can be concluded that Public Perceptions of Regional Regulation No. 12 of 2008 in Fostering Child Singers in Tampan District are in the "Not Good" range.Key Words: Studies, Perceptions, Society, Local Regulations Fostering Child Singers.